Monitoring Perubahan Penggunaan Lahan Pesisir di Kabupaten Gianyar Menggunakan Citra Landsat 1997 dan 2018 - Wardimas, Kadek Ayun; Nuarsa, I Wayan; Putra, I Dewa Nyoman Nurweda (Journal of Marine and Aquatic Sciences; Vol 7 No 2 (2021)DO - 10.24843/jmas.2021.v07.i02.p16, 2021)
The sustainable development process followed by high population growth is an important factor causing land conversion in coastal areas. Analysis of change and planning of land use is one form of coastal resource management to reduce land damage so that it can be used sustainably. This study aims to determine the types and changes in land use over 21-year period (1998-2018) in the coastal area of Gianyar Regency. This study also wants to examine the level of accuracy of Landsat imagery in land use classifications. The Landsat imagery used in this study was Landsat 7 ETM+ in 1998 and Landsat 8 Oli in 2018. The classification method chosen was the supervised classification with the Maximum Likelihood method. The software used is SAGA GIS to process images and QGIS to design map layouts. The results showed that the land use classes in the study area were water, bare land, settlements and buildings, shrubs/bushes, rice fields, moor and mixed gardens. In the period 1998-2018, four classes experienced declined in area, namely water (1.71 ha), bare land (54.99 ha), mixed gardens (28.08 ha), and rice fields (226.62 ha). Meanwhile, land use classes that have increased in area are shrubs/bushes (44.28 ha), moor (104.58 ha), and settlements and buildings (162.54 ha). The overall level of accuracy in land use classification is 85%.